Fostering Students’ Tolerance in Civic Education: An Experimental Study of Value Clarification Technique Assisted by Picture Cards - Permani, Made Intan; Sanjaya, Dewa Bagus; Suastika, I Nengah (Jurnal Paedagogy, 2026)
This study aims to examine the effect of the Value Clarification Technique (VCT) assisted by picture cards on enhancing students’ tolerance attitudes in Civic Education. The study employed a quasi-experimental method using a pretest–posttest control group design. The participants consisted of 60 fifth-grade students from a public elementary school in Bali, Indonesia, who were divided into an experimental group and a control group. The experimental group received instruction using the Value Clarification Technique assisted by picture cards, while the control group received conventional instruction. The instrument used in this study was a 20-item Likert-scale questionnaire designed to measure students’ tolerance attitudes. Data were analyzed using descriptive statistics, normality and homogeneity tests, paired-samples t-test, and independent-samples t-test. The results showed that students in the experimental group achieved a higher posttest mean score (M = 86.43) compared with those in the control group (M = 75.87). The independent-samples t-test revealed a statistically significant difference between the two groups, t(58) = 3.884, p < 0.001, with a large effect size (Cohen’s d = 1.00). These findings indicate that the implementation of the Value Clarification Technique assisted by picture cards had a significant effect on improving students’ tolerance attitudes. The integration of reflective learning through the Value Clarification Technique and visual support through picture cards enabled students to understand and internalize tolerance values more meaningfully during classroom interactions.